Respuesta :

this is how it’s written out
Ver imagen rubriam412

The equation [tex]x^{3} - 3[/tex] has x values as 0, [tex]\sqrt{3}[/tex] and -[tex]\sqrt{3}[/tex].

We are given,

3 is subtracted from the cube of a number.

Let the number be x then we can write it as:

 [tex]x^{3}[/tex] - 3

We are to solve for x.

We can write the equation as:

[tex]x^{3}[/tex] - 3  = 0

x ( [tex]x^{2}[/tex]- 3 ) = 0

x = 0 and ( [tex]x^{2}[/tex] - 3 ) = 0

x = 0 and [tex]x^{2}[/tex] = 3

x = 0 and x = ±[tex]\sqrt{3}[/tex]

So we have,

x  = 0, [tex]\sqrt{3}[/tex] and -[tex]\sqrt{3}[/tex]

Thus we have x values as 0, [tex]\sqrt{3}[/tex] and -[tex]\sqrt{3}[/tex].

Learn more about solving equations for x here:

https://brainly.com/question/2623597

#SPJ2